Question:

If \( \alpha + i\beta \) and \( \gamma + i\delta \) are the roots of the equation \( x^2 - (3-2i)x - (2i-2) = 0 \), \( i = \sqrt{-1} \), then \( \alpha\gamma + \beta\delta \) is equal to:

Show Hint

For complex roots, use the quadratic formula to find the roots and compute products directly.
Updated On: Feb 5, 2025
  • 6
  • 2
  • -2
  • -6
Hide Solution
collegedunia
Verified By Collegedunia

The Correct Option is B

Solution and Explanation

We solve the quadratic equation \( x^2 - (3-2i)x - (2i-2) = 0 \) using the quadratic formula: \[ x^2 - (3 - 2i) x - (2i - 2) = 0 \] \[ x = \frac{(3 - 2i) \pm \sqrt{(3 - 2i)^2 - 4(1)(-(2i - 2))}}{2(1)} \] \[ = \frac{(3 - 2i) \pm \sqrt{9 - 4i^2 - 4(1)(-2i + 2)}}{2} \] \[ = \frac{3 - 2i \pm \sqrt{9 - 4(-1) - 12i + 8i - 8}}{2} \] \[ = \frac{3 - 2i \pm \sqrt{-3 - 4i}}{2} \] \[ = 3 - 2i \pm \sqrt{(1)^2 + (2i)^2 - 2(1)(2i)} \] \[ = 3 - 2i \pm (1)^{2} + (2i)^{2} - 2(1)(2i) \] \[ = 2 - 2i or 1 + 0i \] So \( \alpha \beta = 2(1) \cdot (-2)(0) = 2 \).
Was this answer helpful?
0
0

Top Questions on Matrices and Determinants

View More Questions